The Effect of Motivation and Work Environment on Employee Performance at PT. Indo Suhar Jaya Bogor Branch - Melistiana Rachmawati; Taat Kuspriyono; Lady Diana Warpindyastuti (Penerbit Jurnal Indonesia, 2023)
This research aims to knowing the effect of motivation and work environment on employee performance of PT Indo Suhar Jaya Bogor Branch. The population of employees of PT Indo Suhar Jaya Bogor Branch was 110 employees. sampling in this study using the slovin formula as many as 52 employees. The data was collected through using a Likert scale that was administered using Microsoft Excel 2013 software and IBM SPSS Statistic 26 software. The research methods will be used in the form of a validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, t test and f test. This study has 3 findings in accordance with the hypothesis proposed, namely: (1) that motivation has a positive and significant effect on employee performance, (2) that the work environment has a positive and significant effect on employee performance, (3) that motivation and work Environment have a positive effect on employee performance.